THE DYNAMICS OF COGNITION IN CLIL: INTEGRATING CONTENT AND LANGUAGE IN THE CLASSROOM - George, Arun (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Cognition is a critical factor in the effectiveness of Content and Language Integrated Learning (CLIL). In classrooms where subject content drives communication, cognitive development is enhanced through the integration of language and meaningful content. This reciprocal relationship between content and language not only supports language acquisition but also deepens subject understanding. This paper explores the key elements that contribute to successful cognitive development in CLIL classrooms, with a focus on strategies and practices that enhance both content learning and language proficiency.